Rapid solidification of ternary Nb‐Y‐Ni immiscible alloys. Issue 9 (18th September 2020) - Zheng, W.; Yu, J.; Xin, L.; Su, M.; Fu, D.; Zhang, F.
Abstract: The rapid solidification experiments have been carried out for the Nb(45‐x) Yx Ni55 (x = 9, 19, and 27) alloys. The microstructure characterization shows the occurrence of the liquid‐liquid phase separation into the Niobium‐rich and Yttrium‐rich liquids. The Niobium‐rich spherical particles were embedded in the glassy Yttrium‐rich matrix for the alloy Nb36 Y9 Ni55, while glassy Yttrium‐rich ones were located in the glassy Niobium‐rich matrix for the alloy Nb18 Y27 Ni55 . A structure of hierarchical separation was detected in the as‐quenched alloy Nb26 Y19 Ni55 . The size distribution of the spherical particles in the as‐quenched Nb(45‐x) Yx Ni55 (x = 9 and 27) alloys ranges from several nanometers to sub micrometer and is close to the Gaussian distribution. The average diameters of the Niobium‐rich particles in the as‐quenched Nb36 Y9 Ni55 alloy and the Yttrium‐rich particles in the Nb18 Y27 Ni55 alloy are 0.23 μm and 0.15 μm, respectively. A dual‐glass structure in the as‐quenched Nb18 Y27 Ni55 alloy ribbon was determined by X‐ray diffraction and transmission electron microscopy. Abstract : Niobium‐Yttrium‐Nickel alloy with different mean composition for Niobium and Yttrium showed very interesting microstructures and morphologies. The size of the spherical particles ranges from several nanometers to sub micrometer. Improved properties are possibly achieved from this phase‐separated glass with such a small spherical particles embedded in the matrix.